Effects of artificial management on culm properties of Dendrocalamus brandisii - Yan, Yingdan; Yang, Chuanfei; Wu, Yufang; Liu, Jiaxin; Wang, Shuguang (Frontiers in Plant Science, 2024)
The artificial cultivation and management were extensively carried out in Dendrocalamus brandisii stands. However, the influences of artificial management on the anatomical and chemical characteristics of the bamboo culms were unknown. In this study, the fiber morphology, chemical composition and sugar accumulation of the D. brandisii culms with management and without management were compared in order to determine the influences of artificial management on bamboo culms. The results indicated that artificial management had a significant influence on the fiber morphology, resulting in shorter fiber length, larger L/T ratio, and smaller W/Lu value. However, the management not only increased the contents of moisture, ash, SiO2, and extractive, but also increased the holocellulose contents and decreased the lignin contents, as compared to those without management. Moreover, the management significantly increased the endogenous carbohyrates storage in the culms so as to improve the shoot production. The bamboos under management conditions could still be utilized as a raw material for papermaking. This provided a theoretical basis for the artificial management of D. brandisii stands.